Um modelo matemático de otimização da mistura de diferentes variedades de açúcar para atender ao padrão de qualidade de países importadores - Barbosa, Davi Prates Oliveira (2016)
In this dissertation a mathematical model is developed to establish the weight ratio of sugar's varieties in a mixture directed to the export of the product, where are filled some quality requirements. Currently, Brazil is one of the world's largest sugar exporters, with an export volume estimated at 32.6 million tons for the harvest 2019. To meet the quality requirements of importing countries, it is necessary to combine the sugar's varieties with different characteristics. The proposed model presents an objective function that minimizes the total cost of the blend, respecting these minimum and maximum characteristics required for each export market. The mathematical model is designed as a Linear Programming problem. The results were presented from the analysis of a case study, where the data have been validated in the General Algebraic Modeling System software (GAMS).